A real time colorimetric 'two in one' kit for tracking ppb levels of uric acid and Hg2+ in live HeLa S3 cells and Hg2+ induced keto–enol tautomerism. Issue 67 (1st July 2016) - Kumari, Chanda; Sain, Dibyendu; Kumar, Ashish; Debnath, Sushanta; Saha, Partha; Dey, Swapan
Abstract : A TBET based 'turn-on' fluorescent reagent with high Stokes shifts, exhibits selective and colorimetric detection of biologically important uric acid as well as toxicHg 2+ . Abstract : A TBET based 'turn-on' fluorescent reagent with high Stokes shifts, exhibits selective and colorimetric detection of biologically important uric acid as well as toxicHg 2+ . A newHg 2+ induced keto–enol tautomerism phenomenon associated with a solvatochromic effect was reported. The sensor has proved its real time application as an accurate 'two in one' kit for tracking uric acid andHg 2+ in live HeLa cells via a fluorescence bio-imaging technique.